Impact of lignin removal on the enzymatic hydrolysis of fermented sweet sorghum bagasse. (15th December 2015) - Yan, Zhipei; Li, Jihong; Li, Shizhong; Chang, Sandra; Cui, Ting; Jiang, Yan; Cong, Guangtao; Yu, Menghui; Zhang, Lei
Highlights: Impact of delignification on recalcitrance of FSSB was related to pretreated method. NaOH loading is the key factor to affect sodium hydroxide pretreatment efficiency. Pretreatment time is the dominant factor for calcium hydroxide pretreatment. Ca(OH)2 is more capable of removing surface lignin. Abstract: The complete utilization of sweet sorghum stalks including the fermentable sugars and the lignocellulosic faction is necessary to decrease the bioethanol production cost. Moreover, bioethanol yields from lignocellulosic resources depend on the saccharification efficiency of cellulose. Lignin has been considered as an important factor influencing enzymatic hydrolysis of lignocellulose. In this study, the impact of lignin removal on enzymatic hydrolysis was investigated using fermented sweet sorghum bagasse (FSSB) delignified by NaOH or Ca(OH)2 pretreatments. For NaOH pretreated samples, a positive correlation between cellulose conversion rate and lignin removal was found when the lignin removal was from 8.96% to 65.61%. Further delignification of FSSB did not increase the efficiency of enzymatic hydrolysis. For Ca(OH)2 pretreatment, there was no obvious correlation between lignin removal and cellulose conversion rate. More interestingly, the cellulose conversion rate of FSSB pretreated with Ca(OH)2 was significantly higher than that of FSSB pretreated with NaOH when the same amount of lignin was removed. The surface lignin coverage of FSSB pretreated with 10% NaOH was 1.52 times higher than that of FSSB pretreated with Ca(OH)2 . These results demonstrated that the impact of lignin removal on enzymatic hydrolysis of FSSB pretreated with NaOH and Ca(OH)2 was different. The lignin removal was the main factor influencing the enzymatic hydrolysis of FSSB pretreated with NaOH, while Ca(OH)2 was more capable of removing surface lignin when the lignin content of the samples was similar.